Somatotype profiles of Slovak and Saudi Arabian male soccer players according to playing positions - Kaplánová, Adriana (Array, 2020)
Somatotype of the human body is influenced by many factors. In addition to genetic, there are also environmental factors and cultural differences. The aim of this study was to compare the morphological configuration of men’s body of Slovak and Saudi Arabian soccer players and find out the differences between soccer players in different the playing positions. The study sample consisted of 50 Slovak soccer players aged 19-26 years (21.28±1.46), including 18 defenders, 13 forwards, six goalkeepers, and 13 midfielders, and 50 Saudi Arabian soccer players aged 18-25 years (20.12±1.77), including 16 defenders, 20 forwards, four goalkeepers, and 10 midfielders. The used Heath-Carter method categorize people into 13 groups according to the predominant physical component. The results indicated that soccer players differed among themselves according to playing positions. Slovak defenders and forwards were balanced mesomorphs, Slovak goalkeepers were endomorphic mesomorphs and central type was the predominant in Slovak midfielders. Almost all Saudi Arabian soccer players were predominantly mesomorph-endomorphs, with the exception of the defenders who were endomorphic mesomorphs. On average, the predominant somatotype of Slovak soccer players was balanced mesomorph (2-8,4-1,2-4), and of Saudi Arabian soccer players mesomorph-endomorph (3-8,4-3,1-4). It seems that the somatotype of soccer players varies depending on the country as well as the playing position. Therefore, it is necessary to examine anthropometry also with regard to geographical and cultural differences. In addition, regular evaluation of soccer player’s somatotype can help coaches implement exercise elements that would probably increase players’ sports performance.